Can Levothyroxine Be Taken as Evening Dose? Comparative Evaluation of Morning versus Evening Dose of Levothyroxine in Treatment of Hypothyroidism. (14th July 2011) - Rajput, Rajesh; Chatterjee, Sumanto; Rajput, Meena
Abstract : 152 drug naïve primary hypothyroid patients were divided into morning (Group 1) and evening (Group 2) dosing group and evaluated for change in biochemical profile, physical functioning and Quality of Life during the course of 12 weeks of study. At the end of 12 weeks 70 (90.90%) subjects in Group 1 and 72 (96%) in Group 2 achieved euthyroidism. On evaluation clinical symptoms and total clinical scores improved in both the groups at the end of 6 and 12 weeks. Significant improvement in thyroid profile was seen in both the groups at the end of 6 and 12 weeks (P value <.0001). On intergroup comparison, no significant difference in thyroid profile was seen at 6 and 12 weeks between the morning and the evening dose group. Similar dose of levothyroxine was required to achieve euthyroidism in both the groups. Though an early restoration of euthyroidism was seen in evening group, the difference when compared to the morning group was not statistically significant. On assessment of QoL, statistically significant improvement in various parameters was seen in both the groups. Hence, from the study we inferred that evening dose is as efficacious as morning dose and provides an alternate dosing regimen.